Don't assume, be assured : don't be a fool, check your poo - Tan, Irwin Kin Wei (Nanyang Technological University, 2020)
This paper discusses Don’t Assume, Be Assured (DABA), a health communication campaign targeted at Singaporeans and PRs in their forties to promote earlier detection of colorectal cancer. As governmental and institutional efforts are largely targeted towards the most at-risk group of those above the age of 50, younger Singaporeans remain unaware of their increasing risk of developing colorectal cancer. In a bid to equip this group with means to better identify possible signs and symptoms of colorectal cancer, DABA was kickstarted by four final-year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University, to raise awareness about the rising incidence of colorectal cancer among Singaporeans below the age of 50, as well as to encourage the adoption of stool checking to aid in spotting potential signs and symptoms of the cancer. Three-quarters of colorectal cancer cases in those under the age of 50 fall within ages 40 to 49. As such, by encouraging regular stool checks and visiting a general physician when faced with any anomalies in their stools, DABA also highlighted the importance of keeping one’s health in check instead of brushing off potential symptoms. Guided by the Health Belief Model, DABA sought to increase levels of Perceived Susceptibility, benefits, and Self-efficacy among our target audience to spur the uptake of this behaviour. This paper details the campaign’s process, which includes formative research, strategic development, campaign execution, and evaluation. Further recommendations for future campaigns based on insights gained from DABA are also discussed at the end of this paper.